Effect of dietary daidzein supplementation on reproductive performance, egg quality and bone mineralization in laying hens at first-cycle of production via reproductive-growth axis - Uchechukwu Edna Obianwuna; Xinyu Chang; Rupeng Wu; Hai-jun Zhang; Kai Qiu; Shu-geng Wu (Italian Journal of Animal Science)
Daidzein (Da), an isoflavone, resembles natural oestrogen in structure and activity. We investigated the effects of dietary Da on the reproductive performance, egg quality, and bone mineralisation of hens in the pre-peak laying period. A total of 432 laying hens (110 days) were randomly allocated to control (CON) or Da-supplemented diet (10, 25, and 50 mg/kg). Each treatment had six replicates of 18 birds/replicate, and the feeding trial lasted 8 weeks. Supplementation of dietary Da significantly improved laying rate, egg weight, egg mass, and feed-to-egg ratio (p < 0.05). Likewise, dietary Da significantly improved albumen quality (Haugh unit, thick albumen fraction, and albumen proportion) and eggshell quality (eggshell; strength, eggshell thickness, gloss, and colour) (p < 0.05). Dietary Da exerted a notable significant increase (p < 0.05) on magnum weight, follicle numbers, serum levels of growth hormones, thyroid hormones (T3 and T4), reproductive hormone (oestrogen, follicle-stimulating hormone, luteinizing hormone), and mRNA expression of related genes (ESR1, FSHR1, PRL1, GNHR1). Also, Da significantly increased serum levels of superoxide dismutase, catalase, glutathione and decreased malondialdehyde (p < 0.05). Furthermore, the Da groups showed enhanced tibia strength, length, phosphorus, and bone mineral content (p < 0.05). In summary, dietary Da enhanced early onset of lay and improved albumen, eggshell, and bone quality in laying hens during the pre-peak period. Positive outcomes may be due to the efficient metabolism of Da and the safety level of inclusion. The enhancement of reproductive hormones, related genes, and antioxidant enzymes may explain daidzein’s effects on laying hens.Highlights Daidzein improved egg production significantly. Albumen, eggshell and tibia quality were enhanced. Optimal inclusion level at 25 or 50 mg/kg was safe.